AL DJANAZA OR THE MODEL OF THE TRIPTYCH. FUNERAL ROUTES IN BEJAIA - Abderrahim Kebache; Siham Bestandji (International Journal of Innovative Technologies in Social Science, 2024)
The Al Djanaza route follows Islamic funerary customs. Technically, it involves transporting a body from one location to the cemetery. An anthropological study was conducted in Bejaia, Algeria, with a socio-spatial observation unit established. The research focused on the urban funeral route (UFR), including the Sidi Abderrahmane cemetery, the Sidi Soufi mosque, and the departure point of the body. This social and spatial whole encompasses both funerary practices and the locations where they occur. The aim was to establish a poetics of UFRs. To achieve this, we employed an anthropological approach, particularly through situational observation techniques. The results presented in this article highlight the emergence of a tripartite model -House-Mosque-Cemetery-structuring the sequences that constitute Al Djanaza, along with the dual conventional and differentiated dimensions of the UFR, and its characterization of a triple marking: chronological, gendered, and spatial.